التصوف في بغداد في القرن السادس الهجري - محمد، أحمد إبراهيم عيسى (جامعة المنيا - كلية دار العلوم, 2023)
يعد العصر العباسي الأخير من العصور الإسلامية الزاهرة، حيث أن الخلفاء العباسيين يهتمون بأهل العلم في هذا الزمن، بل كان الخلفاء أنفسهم من محبي العلم ومشجعيه؛ ولذلك ازدهر العلم، وكان الخلفاء يعقدون المجالس للعلم وللمناظرة بحضور عدد كبير من رجال العلم والفقهاء، إذ شهدت بغداد وبلاد المشرق الإسلامي في هذا القرن ألوانا من المجالس العلمية، اختلفت أغراضها ومصدرها وأماكن انعقادها. وكان لمدن كثيرة في المشرق الإسلامي دور كبير في تشجيع واحتضان العلماء والفقهاء والأدباء كنيسابور ومرو وأصفهان، وشيراز وهمذان وسمرقند وغيرها من المدن، على الرغم من معاناة هؤلاء العلماء والفقهاء في ظل التطورات السياسية التي شهدتها بغداد وبلاد المشرق الإسلامي، وذلك بعد دخول السلاجقة مدينة بغداد وهيمنتهم على الخلافة العباسية، والسياسة التي أتبعوها تجاه الخلفاء العباسيين. ظلت بغداد وأمصار الدولة الإسلامية مركزا للحياة العلمية نتيجة لتشجيع الخلفاء العباسيين ورعايتهم للعلم وأهله، وتعددت مراكز نشر العلم والثقافة كالمسجد والمدارس وخزائن الكتب والربط، وامتدت المجالس العلمية إلى قصور الخلفاء والأمراء والسلاطين والوزراء وبيوت العلماء، فكان لها دور هام في نشر العلم والمعرفة في مختلف أمصار الدولة الإسلامية، وانقسمت المجالس العلمية، ما بين المجالس العلمية الخاصة، والمجالس العلمية العامة. Scientific life and the nature of Sufism in Baghdad in the sixth century AH The last Abbasid era is considered one of the prosperous Islamic eras, as the Abbasid caliphs care about the people of knowledge in this time, and the caliphs themselves were lovers and fans of science; Therefore, science flourished, and the Caliphs held councils for science and debate in the presence of a large number of scholars and jurists, as Baghdad and the countries of the Islamic East witnessed in this century a variety of scientific councils, the purposes, source and venues of which differed. Many cities in the Islamic East had a great role in encouraging and embracing scholars, jurists and writers, such as Knysapur, Merv, Isfahan, Shiraz, Hamadhan, Samarkand and other cities, despite the suffering of these scholars and jurists in light of the political developments that Baghdad and the countries of the Islamic East witnessed, after the Seljuks entered the city of Baghdad and their hegemony On the Abbasid Caliphate, and the policy they followed towards the Abbasid Caliphs. Baghdad and the cities of the Islamic State remained a center for scientific life as a result of the encouragement of the Abbasid caliphs and their care for science and its people, and there were many centers for the dissemination of science and culture such as mosques, schools, bookcases and interconnections. The Islamic state, and the scientific councils were divided between private scientific councils and general scientific councils.
Keywords: التصوف الإسلامي -- الفكر الصوفي -- المجالس العلمية -- العصر العباسي -- العراق